The roads ahead: Narratives for shared socioeconomic pathways describing world futures in the 21st century. (January 2017) - O'Neill, Brian C.; Kriegler, Elmar; Ebi, Kristie L.; Kemp-Benedict, Eric; Riahi, Keywan; Rothman, Dale S.; van Ruijven, Bas J.; van Vuuren, Detlef P.; Birkmann, Joern; Kok, Kasper; Levy, Marc; Solecki, William
Highlights: We present narrative descriptions of future societal development associated with the shared socioeconomic pathways. We describe the methods used to develop the narratives and how they produce particular combinations of challenges to mitigation and adaptation. The narratives describe plausible future changes in demographics, human development, economy, institutions, technology, and environment. The narratives span an uncertainty space in terms of socioeconomic challenges to adaptation and mitigation of climate change. The narratives relate to Sustainability, Regional Rivalry, Inequality, and Fossil-fueled Development, and a Middle of the Road pathway. Abstract: Long-term scenarios play an important role in research on global environmental change. The climate change research community is developing new scenarios integrating future changes in climate and society to investigate climate impacts as well as options for mitigation and adaptation. One component of these new scenarios is a set of alternative futures of societal development known as the shared socioeconomic pathways (SSPs). The conceptual framework for the design and use of the SSPs calls for the development of global pathways describing the future evolution of key aspects of society that would together imply a range of challenges for mitigating and adapting to climate change. Here we present one component of these pathways: the SSP narratives, a set of five qualitative descriptions of future changes in demographics, human development, economy and lifestyle, policies and institutions, technology, and environment and natural resources. We describe the methods used to develop the narratives as well as how these pathways are hypothesized to produce particular combinations of challenges to mitigation and adaptation. Development of the narratives drew on expert opinion to (1) identify key determinants of these challenges that were essential to incorporate in the narratives and (2) combine these elements in the narratives in a manner consistent with scholarship on their inter-relationships. The narratives are intended as a description of plausible future conditions at the level of large world regions that can serve as a basis for integrated scenarios of emissions and land use, as well as climate impact, adaptation and vulnerability analyses.